(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
The main objective of the research is to present a proposal for a design methodology aimed at creating characters. Each of its stages with due explanations were presented throughout the text of the work. To structure the methodology, authors from the field of design, comics and character creation were researched. With the study it was possible to understand what to include in a generic design methodology to meet the needs of creating a character. Bruno Munari’s studies were the basis for adapting and developing the methodology applied to character design.